U-Omp19 from Brucella abortus is a Useful adjuvant for Vaccine Formulations against Salmonella infection in Mice - Risso, Gabriela Sofía (2017)
Most pathogens infect through mucosal surfaces, and parenteral immunization typically fails to induce effective immune responses at these sites. Development of oral-administered vaccines capable of inducing mucosal as well as systemic immunity while bypassing the issues of antigen degradation and immune tolerance could be crucial for the control of enteropathogens. This study demonstrates that U-Omp19, a bacterial protease inhibitor with immunostimulatory features, coadministered with Salmonella antigens by the oral route, enhances mucosal and systemic immune responses in mice. U-Omp19 was able to increase antigen-specific production of IFN-γ and IL-17 and mucosal (IgA) antibody response. Finally, oral vaccination with U-Omp19 plus Salmonella antigens conferred protection against virulent challenge with Salmonella Typhimurium, with a significant reduction in bacterial loads. These findings prove the efficacy of this novel adjuvant in the Salmonella infection model and support the potential of U-Omp19 as a suitable adjuvant in oral vaccine formulations against mucosal pathogens requiring T helper (Th)1-Th17 protective immune responses.